2003
DOI: 10.1046/j.1365-3091.2003.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

A depositional model for the terminal Neoproterozoic–Early Cambrian Ara Group evaporites in south Oman

Abstract: Six evaporite–carbonate sequences are recognized in the terminal Neoproterozoic–Early Cambrian Ara Group in the subsurface of Oman. Individual sequences consist of a lower, evaporitic part that formed mainly during a lowstand systems tract. Overlying platform carbonates contain minor amounts of evaporites and represent transgressive and highstand systems tracts. Detailed sedimentological and geochemical investigation of the evaporites allowed reconstruction of the depositional environment, source of brines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 35 publications
(73 reference statements)
2
57
0
Order By: Relevance
“…Sulfide mineralization is common in cap rocks of salt domes trapping hydrocarbons (Schröder et al, 2003). Hydrothermal mineralization (e.g., well-crystalline hematite, galena, pyrite, and fluorite) is common within the Hormuz series (Ala, 1974;Salah, 1996;Schrö der et al, 2003). The strong correlation of Fe, Ni, Cu, and Zn might suggest the input of a mineralizing fluid from some deep source, or associated with rift-related igneous activity in the Hormuz series .…”
Section: Discussionmentioning
confidence: 99%
“…Sulfide mineralization is common in cap rocks of salt domes trapping hydrocarbons (Schröder et al, 2003). Hydrothermal mineralization (e.g., well-crystalline hematite, galena, pyrite, and fluorite) is common within the Hormuz series (Ala, 1974;Salah, 1996;Schrö der et al, 2003). The strong correlation of Fe, Ni, Cu, and Zn might suggest the input of a mineralizing fluid from some deep source, or associated with rift-related igneous activity in the Hormuz series .…”
Section: Discussionmentioning
confidence: 99%
“…In strata beneath the modern day South Oman Salt Basin (SOSB), the Ara Group exists as a series of six carbonate-evaporite shallowing-upward cycles (Fig. 3), deposited in a strongly subsiding block-faulted basin (Grotzinger et al, 2002;Amthor et al, 2003;Schrö der et al, 2003b). The basal Ara unit (A0) is believed to have been deposited prior to the onset of periodic basin restriction based on the absence of evaporites and/or evaporitic enrichment in e.g., d 13 C carb /d 18 O carb (Amthor et al, 2003).…”
Section: Geologic Contextmentioning
confidence: 99%
“…3b, Schrö der et al, 2004), which have been shown to originate from marine waters (Horita et al, 2002;Schrö der et al, 2003a;Brennan et al, 2004). Despite the evaporitic conditions associated with primary evaporite deposition, stratiform anhydrite is believed to accurately record the isotopic composition of seawater sulfate because of nearly quantitative removal of seawater sulfate and the small ($1.6&) isotopic fractionation associated with gypsum/anhydrite deposition (Raab and Spiro, 1991).…”
Section: The Ara Anomaly: D 34 S Pyrmentioning
confidence: 99%
“…High rates of accumulation of organic matter indicate that bottom waters were anoxic (Kirkland, 2003). The development of a barrier caused restriction of the basin, associated with relatively stable arid climatic conditions, allowing deposition of a thick prograding succession, similar to that described by Schroder et al (2003) in the Early Cambrian Ara Group in Oman. Kendall (1992) indicated that low-lying basins with a flat basin floor are flooded rapidly leading to rapid establishment of open-marine conditions.…”
Section: Sequence Stratigraphymentioning
confidence: 78%